2022
DOI: 10.3390/ijerph19116874
|View full text |Cite
|
Sign up to set email alerts
|

Educational Interventions to Promote Cervical Cancer Screening among Rural Populations: A Systematic Review

Abstract: The urban–rural gap in cervical cancer screening uptake is a significant public health consideration. Educational interventions are commonly adopted to promote cervical cancer screening among females in rural areas; however, the characteristics and effectiveness of these educational interventions remain unclear. In this review, we aimed to identify the characteristics of educational interventions used in rural populations and to evaluate the effects of these interventions on cervical cancer screening-related o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 53 publications
1
19
0
5
Order By: Relevance
“…We found a significant relationship between knowledge of CC screening and acceptability among female undergraduates of Babcock University. A systematic review of educational interventions to promote CC screening reported that educational interventions improved the knowledge and uptake of CC screening [26]. Furthermore, we found a significant relationship between the age of the respondents and their acceptance of CC screening.…”
Section: Discussionmentioning
confidence: 49%
“…We found a significant relationship between knowledge of CC screening and acceptability among female undergraduates of Babcock University. A systematic review of educational interventions to promote CC screening reported that educational interventions improved the knowledge and uptake of CC screening [26]. Furthermore, we found a significant relationship between the age of the respondents and their acceptance of CC screening.…”
Section: Discussionmentioning
confidence: 49%
“…However, the pooled effects of health education was not estimated and reported as the effectiveness are different based on the study setting, populations and the way of delivery [ 53 ]. Recently published systematic review reported that the effect of educational interventions among rural women increased the uptake of CCS (RR, 1.26, 95% CI 1.10 to 1.45; 2 studies, 663 women,; I 2 = 9%) [ 54 ]. A narrative review conducted among lower socioeconomic group in HICs reported that HPV self-testing can improve uptake of cervical cancer screening among lower socioeconomic groups.…”
Section: Discussionmentioning
confidence: 99%
“…19 While higher education and income levels were associated with higher uptake in different studies, a recommendation from a friend or healthcare professional was the most reported facilitator. 20 The uptake of cervical cancer screening can vary depending on several factors, such as access to screening services, awareness of the importance of screening, and individual beliefs and attitudes about the test. Universal emotional reasons include embarrassment, fear of the test and the results or poor previous experiences.…”
Section: Barriers To the Effective Delivery Of The Cervical Screening...mentioning
confidence: 99%